The Role of Primary Cilia in Thyroid Cancer: From Basic Research to Clinical Applications - Ma, Cheng-Xu; Ma, Xiao-Ni; Li, Ying-Dong; Fu, Song-Bo (Frontiers in Endocrinology, 2021)
Primary cilia (PC) are microtubule-based organelles that are present on nearly all thyroid follicle cells and play an important role in physiological development and in maintaining the dynamic homeostasis of thyroid follicles. PC are generally lost in many thyroid cancers (TCs), and this loss has been linked to the malignant transformation of thyrocytes, which is regulated by PC-mediated signaling reciprocity between the stroma and cancer cells. Restoring PC on TC cells is a possible promising therapeutic strategy, and the therapeutic response and prognosis of TC are associated with the presence or absence of PC. This review mainly discusses the role of PC in the normal thyroid and TC as well as their potential clinical utility.